Inhibition of the histone demethylase JMJD2E by 3-substituted pyridine 2,4-dicarboxylates. - Thalhammer, A; Mecinović, J; Loenarz, C; Tumber, A; Rose, N; Heightman, T; Schofield, C (2011)
Based on structural analysis of the human 2-oxoglutarate (2OG) dependent JMJD2 histone N(ε)-methyl lysyl demethylase family, 3-substituted pyridine 2,4-dicarboxylic acids were identified as potential inhibitors with possible selectivity over other human 2OG oxygenases. Microwave-assisted palladium-catalysed cross coupling methodology was developed to install a diverse set of substituents on the sterically demanding C-3 position of a pyridine 2,4-dicarboxylate scaffold. The subsequently prepared di-acids were tested for in vitro inhibition of the histone demethylase JMJD2E and another human 2OG oxygenase, prolyl-hydroxylase domain isoform 2 (PHD2, EGLN1). A subset of substitution patterns yielded inhibitors with selectivity for JMJD2E over PHD2, demonstrating that structure-based inhibitor design can enable selective inhibition of histone demethylases over related human 2OG oxygenases.